Effect of Polypropylene Fiber on Properties of Alkali-Activated Slag Mortar - Yangchen Xu; Haiming Chen; Pengju Wang (Advances in Civil Engineering)
Alkali-activated slag (AAS) is becoming an increasingly popular building material due to its excellent engineering properties and low CO2 emissions, but its large shrinkage is an important reason to restrict its application and popularization. This work is aimed to study the possibility of inhibiting the shrinkage of AAS mortar by incorporating polypropylene fiber (PPF). For this, an experimental study was carried out to evaluate the effects of PPF content on setting time, fluidity, physical properties, mechanical properties, impact resistance, and microstructure of AAS mortar. The volume content of PPF is 0.05%, 0.1%, 0.15%, and 0.2%. The working, physical (porosity, water absorption, and bulk density), mechanical, shrinkage, and impact resistance properties of the AAS mortars were evaluated. The results show that incorporating PPF effectively reduces the shrinkage deformation of AAS mortar, significantly improves its impact resistance, enhances its toughness, and slightly improves its compressive strength in the later stage. At the same time, PPF delays the initial setting time of AAS mortar and reduces the fluidity, density, porosity, and water absorption of AAS mortar. SEM results show that the bridging effect of PPF between AAS mortars can inhibit the generation and propagation of cracks, improve the internal microstructure, and enhance the performance of AAS mortar.